Pengalaman Akseptor KB dalam Menggunakan Metode KB Suntik Depo Medroxyprogesterone Acetate (DMPA) di PMB Bidan “K” - Eka Mirah Apriyati; Rita Ayu Yolandia; Siti Rafika Putri (Indonesia Journal of Midwifery Sciences, 2023)
Introduction: 3-month injectable contraception, if there are advantages, there must be disadvantages to using 3-month injectable contraceptives. Adverse effects that can occur with the use of 3-month injectable contraceptives are often found with complaints, including Short and long menstrual cycles, Heavy or light bleeding, Irregular bleeding or spotting, and No menstruation at all (amenorrhoea). Objectives: This study aims to analyze the side effects, effectiveness and sexual intercourse on the experience of family planning acceptors in using the DMPA injection KB method at PMB Midwife K Klapanunggal in 2022. Method: The population in this study was 10 people including the head of PMB (1 person) and DMPA injecting family planning acceptors (9 people). This type of qualitative research used a case study approach. PMB Midwife K. This study began with transcripts of the interview results, after the interview transcripts were completed, the researcher created a matrix to determine the ideas put forward by the informants and group them according to their frame of mind. The resulting data is processed using Microsoft Office software in reducing data, presenting data, drawing conclusions and verifying data. Result: The results showed that the experiences felt by informants were different, including weight continued to increase, discharge of spots constantly, headaches, emotions and spots that make it uncomfortable. Pleasant experiences and feelings during sexual intercourse with a partner affect women's sexual satisfaction and reduce sexual dysfunction. Sexuality, sexual desire and sexual arousal are more influenced by their partner’s mental health and feelings. Conclusion: Family planning acceptors in using DMPA injections have different experiences and side effects, but they are effective in preventing pregnancy, and there is no difference in sexual intercourse.